2004
DOI: 10.1039/b407374f
|View full text |Cite
|
Sign up to set email alerts
|

First observation of capping/uncapping by a ligand of a Zn porphyrin adsorbed on Ag(100)

Abstract: A significant first step towards creation of catalytically active porphyrin-functionalised metal surfaces has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 4 publications
4
68
0
Order By: Relevance
“…2,3,7 Supramolecular arrays are of interest with respect to the study of energy transfer and photosynthetic mechanisms 7,8 while two-dimensional porphyrin assemblies have attracted attention for possible application as chemical sensors, in molecular electronics, or as chemically switchable 2D rotors. 3,9,10 Related to this, we recently showed that a porphyrin-functionalized silver surface exhibits ligand binding and unbinding reactions characteristic of the free metalloporphyrin 11 and showed that a well-chosen ligand can strongly alter the dynamics of adsorbed porphyrins. 10 Porphyrins have been attached to oxide surfaces for use as sensors by means of organophosphonate linkers.…”
Section: Introductionmentioning
confidence: 85%
“…2,3,7 Supramolecular arrays are of interest with respect to the study of energy transfer and photosynthetic mechanisms 7,8 while two-dimensional porphyrin assemblies have attracted attention for possible application as chemical sensors, in molecular electronics, or as chemically switchable 2D rotors. 3,9,10 Related to this, we recently showed that a porphyrin-functionalized silver surface exhibits ligand binding and unbinding reactions characteristic of the free metalloporphyrin 11 and showed that a well-chosen ligand can strongly alter the dynamics of adsorbed porphyrins. 10 Porphyrins have been attached to oxide surfaces for use as sensors by means of organophosphonate linkers.…”
Section: Introductionmentioning
confidence: 85%
“…[12][13][14][15][16][17][18][19][20][21] Most of them are scanning tunneling microscopy/spectroscopy investigations of porphyrins on metal surfaces where the macrocycle is adsorbed flat and the conformation of the meso-substituents will change as a function of the surface termination and the interaction with the substrate. [12][13][14][15][16] There are only a few studies on semiconductor surfaces [17,20] and even fewer experiments using other techniques to extract the porphyrin orientations on surfaces. [18,21] One of these experiments has shown that by changing the macrocycle porphyrin orientation from flat to almost orthogonal to the graphite surface, the function of the system changes as well.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously made a porphyrin-functionalized silver surface that exhibits ligand binding, unbinding and displacement reactions characteristic of the free metalloporphyrin 11 and have also used well-chosen ligands to dramatically alter their dynamics. 12 Such weakly bound systems are unlikely to be sufficiently robust for catalytic applications, however, especially in the presence of a solvent where resistance to leaching is an essential attribute.…”
Section: Introductionmentioning
confidence: 99%